Strategies to handle heterogeneity prevalent within an IOT based network - Pavithra, T; K. R. Sastry, J (International Journal of Engineering and Technology, 2018)
One of the most important features of an IOT network is heterogeneity among the devices, subnets, communication systems, data storage and retrieval. IOT can be conceived to be in existence in hierarchal structure having situated in many layers. In each of the layer there is an element of heterogeneity. The heterogeneity is more severe in the layer which deals with real connect and communication.In this paper different strategies are explored for handling heterogeneity among communication protocols that are used for effecting communication among devices, cluster of devices and the alike